2016
DOI: 10.21037/tau.2016.03.11
|View full text |Cite
|
Sign up to set email alerts
|

Premature ejaculation in type II diabetes mellitus patients: association with glycemic control

Abstract: BackgroundPremature ejaculation (PE) is a highly prevalent sexual dysfunction among patients with diabetes mellitus (DM). Despite this, the underlying mechanism of this association is poorly understood. In this study, we aimed to investigate the prevalence of PE in a group of patients with DM and explore possible associations linking both conditions together.MethodsThis was a prospective study of subjects recruited with advertisement pamphlets and whose sexual function was assessed using the international inde… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
37
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 22 publications
(37 citation statements)
references
References 44 publications
0
37
0
Order By: Relevance
“…Some authors suggest that the longer the erectile problem, the worse the anxiety, and the more marked the PE [73]. Because of performance anxiety regarding their erectile reliability, patients could rush through an intercourse, with PE as a deleterious consequence [74].…”
Section: Discussionmentioning
confidence: 99%
“…Some authors suggest that the longer the erectile problem, the worse the anxiety, and the more marked the PE [73]. Because of performance anxiety regarding their erectile reliability, patients could rush through an intercourse, with PE as a deleterious consequence [74].…”
Section: Discussionmentioning
confidence: 99%
“…The number of studies in this field is far from enough. Bellastella et al showed that type I diabetes was not a risk factor for PE and results from a prospective study demonstrated that PE was more prevalent in patients with diabetes (Bellastella et al., 2015; Majzoub et al., 2016). However, further studies are warranted to validate these findings.…”
Section: Discussionmentioning
confidence: 99%
“…The prevalence of PE was increased in noninsulin-dependent diabetic patients,8586 although the exact pathogenesis of PE in diabetic patients is not well known. It has been proposed that PE in diabetic patients may be secondary to psychogenic factors such as performance anxiety and depression or organic factors such as diabetic neuropathy, which may be implicated in the pathophysiology of PE due to the fact that potency and ejaculation depend on the integrity of the autonomic nervous system and its central and peripheral neurotransmitters 8587.…”
Section: Etiopathogenesis Of Pementioning
confidence: 97%